Relational research and organisation studies - Madsen, Charlotte Øland (Routledge studies in management, organizations and society, 2018)
This volume lays out a variety of ways of engaging in research projects focused on exploring the everyday relational practices of organizing and leading is presented. The main focus is through elaborate examples from the author's own research to further the understanding of how it is possible to carry out relational constructionist research inquiries. The book presents a series of examples ranging from conversations with top-managers, relational action learning processes in management groups, polyphonic inquiries for project management teams, transformative roleplaying in organizations, analyzing organizational dialoguing, and polyphonic future-forming ways of writing up research. Relational Research and Organisation Studies does not only present and discuss guidelines for practice at a onto-epistemological level but also presents and discusses concrete cases of research projects building on relational constructionist ideas. Furthermore, excerpts of data are presented and analyzed in order to explain the co-constructed processes of the inquiries more in detail. Relational Research and Organisation Studies invites the reader into the process of planning and carrying out relational constructionist research inquiries. Based on the authors own experiences, it inspires readers to develop their own relational inquiries within the field of organizing.